PERANCANGAN APLIKASI DASHBOARD WMS BERBASIS WEB SERVICE DENGAN MENGGUNAKAN TEKNOLOGI .NET WEB SERVICE DAN PHP - Ryan Permana; Didiek S Wiyono; Nanang Ismail (JURNAL ISTEK, 2011)
Warehouse Management System needs an item inventory, configuration saving method of items, integration among warehouses, and warehouse finance control. All of the aspects must be well arranged, in order to avoid warehouses’s work performance decrease that can affect to supply chain profit. To avoid the supply chain from losses, a warehouses need a system that can help to maintain and manage all of warehouse’s variables. A system that can implemented is WMS Dashboard. WMS Dashboard is an application that can show the warehouse’s data realtime and with high accuration. WMS Dashboard’s services are made by using ASP.NET Web Service Technology which use SOAP protocol and WSDL interface so it support multi platform system to system communication which using HTTP protocol. The database of WMS Dashboard is made by using MS SQL Server DBMS which has fully compatibility with other applications that made by .NET Framework. Object oriented PHP is need to made the application for client side. WSDL of WMS dashboard application consist of 56 services. The services has been integrated with WMS Dashboard Application which based on PHP, so it would be accessed easily, and it can be used to help maintain and manage the Warehouse System variables.